The Use of Google Classroom Media in Development of Non Print Audio Teaching Material for High School Physics Learning - Nana Nana (PAEDAGOGIA, 2020)
This research uses google classroom media as the essence of developing and utilizing non-printed audio teaching materials for digital high school physics learning. The purpose of this study are: (1) Describe the audio non-print media; (2) Describe the google classroom media; (3) Determine the level of interest from the use of google classroom media in the development and utilization of audio non-printed teaching materials. The research method used in this study is a descriptive qualitative-based development method supported by quantitative data. In this study, a study was conducted that did not make a product design through this research, but only validated or tested the effectiveness, efficiency and practicality of existing products. Therefore, in this study, the effectiveness of Google Classroom in developing non-printed audio teaching materials was tested. The subjects of the study were 2018 physics education students at Siliwangi University, totaling 44 people and the object of this study was the google classroom media as the essence of physics learning in the digital age.